Pengaruh Pelatihan Ketrampilan Sosial Untuk Meningkatkan Penyesuaian Diri Sosial Di Sekolah Pada Remaja Sekolah Menengah Pertama - Hanny Rufaidah Damra (LPPM STAI Diniyah Pekanbaru, 2021)
This study aims to determine the effect of social skills training to improve social adjustment in adolescents at junior high school. The hypothesis in this study is there is an effect of providing social skills training to improve the social adjustment of adolescents in junior high school. This study uses a pretest and posttest design. Respondents in this study amounted to 16 junior high school students. The Social Skill Training (SST) module in this study was arranged based on the stages of implementing SST which refers to the opinion of Ramdhani (2002), social skills training with the stages of modeling, role play, feedback, and transfer training. This module is structured based on aspects of social skills from Gresham and Elliot (1990) which consist of aspects of cooperation, assertiveness, empathy, and self-control. The analysis carried out in this study is using non-parametric statistics. The results show that there are changes in the trainees before and after undergoing training. This means that there is an increase in the ability of social adjustment in the trainees